A=\(\left(3x-5\right).\left(2x+11\right)-\left(2x+3\right).\left(3x+7\right)\)
B=\(\left(2x+3\right).\left(4x^2-6x+9\right)-2\left(4x^3-1\right)\)
C= \(\left(x-1\right)^3-\left(x+1\right)^3+6.\left(x+1\right).\left(x-1\right)\)
D=\(\left(x+y\right)^2-\left(x-y\right)^2\)
=))))) dài ghê
A = (3x - 5) (2x + 11) - (2x + 3) (3x + 7)
= 3x (2x + 11) - 5 (2x + 11) - 2x (3x + 7) + 3 (3x + 7)
= 6x2 - 33x - 10x - 55 - 6x2 - 14x + 9x + 21
= -48x - 34
B = (2x + 3) (4x2-6x+9) - 2(4x3 - 1)
= (8x3 + 27) - 8x3 + 2
= 29
C = (x - 1)3 - (x + 1)3 + 6 (x + 1) (x - 1)
= (x3 - 3x2 + 3x - 1) - (x3 + 3x2 + 3x + 1) + 6 (x2 - 1)
= x3 - 3x2 + 3x - 1 - x3 - 3x2 - 3x - 1 + 6x2 - 6
= 4
D = (x + y)2 - (x - y)2
= (x2 + 2xy + y2) - (x2 - 2xy + y2)
= x2 + 2xy + y2 - x2 + 2xy - y2
= 4xy
bài không đảm bảo đúng 100%, ai thấy có lỗi hay sai ở đâu thì cầu góp ý ^^